Cellular remodeling of fibrotic conduit as vascular graft. (January 2021) - Qiu, Xuefeng; Lee, Benjamin Li-Ping; Wong, Sze Yue; Ding, Xili; Xu, Kang; Zhao, Wen; Wang, Dong; Sochol, Ryan; Dong, Nianguo; Li, Song
Abstract: The replacement of small-diameter arteries remains an unmet clinical need. Here we investigated the cellular remodeling of fibrotic conduits as vascular grafts. The formation of fibrotic conduit around subcutaneously implanted mandrels involved not only fibroblasts but also the trans-differentiation of inflammatory cells such as macrophages into fibroblastic cells, as shown by genetic lineage tracing. When fibrotic conduits were implanted as vascular grafts, the patency was low, and many fibrotic cells were found in neointima. Decellularization and anti-thrombogenic coating of fibrotic conduits produced highly patent autografts that remodeled into neoarteries, offering an effective approach to obtain autografts for clinical therapy. While autografts recruited mostly anti-inflammatory macrophages for constructive remodeling, allogenic DFCs had more T cells and pro-inflammatory macrophages and lower patency. Endothelial progenitors and endothelial migration were observed during endothelialization. Cell infiltration into DFCs was more efficient than decellularized arteries, and infiltrated cells remodeled the matrix and differentiated into smooth muscle cells (SMCs). This work provides insight into the remodeling of fibrotic conduits, autologous DFCs and allogenic DFCs, and will have broad impact on using fibrotic matrix for regenerative engineering. Graphical abstract: Image 1